Different methods of synthesizing poly(glycerol sebacate) (PGS): A review - Godinho, Bruno; Gama, Nuno; Ferreira, Artur (Frontiers in Bioengineering and Biotechnology, 2022)
Poly(glycerol sebacate) (PGS) is a biodegradable elastomer that has attracted increasing attention as a potential material for applications in biological tissue engineering. The conventional method of synthesis, first described in 2002, is based on the polycondensation of glycerol and sebacic acid, but it is a time-consuming and energy-intensive process. In recent years, new approaches for producing PGS, PGS blends, and PGS copolymers have been reported to not only reduce the time and energy required to obtain the final material but also to adjust the properties and processability of the PGS-based materials based on the desired applications. This review compiles more than 20 years of PGS synthesis reports, reported inconsistencies, and proposed alternatives to more rapidly produce PGS polymer structures or PGS derivatives with tailor-made properties. Synthesis conditions such as temperature, reaction time, reagent ratio, atmosphere, catalysts, microwave-assisted synthesis, and PGS modifications (urethane and acrylate groups, blends, and copolymers) were revisited to present and discuss the diverse alternatives to produce and adapt PGS.